Effectiveness of live attenuated influenza vaccine and inactivated influenza vaccine in children during the 2014–2015 season. Issue 20 (9th May 2017) - McLean, Huong Q.; Caspard, Herve; Griffin, Marie R.; Poehling, Katherine A.; Gaglani, Manjusha; Belongia, Edward A.; Talbot, H. Keipp; Peters, Timothy R.; Murthy, Kempapura; Ambrose, Christopher S.
Highlights: Influenza vaccine effectiveness in children was assessed using a test-negative design. In 2014–2015, most influenza cases were caused by a new antigenic cluster of A(H3N2) LAIV and IIV provided similar protection against medically attended A(H3N2) infection. LAIV provided significantly greater protection than IIV against influenza B strains. Abstract: Background: A clinical study found that live attenuated influenza vaccine (LAIV) was superior to inactivated influenza vaccine (IIV) against drifted A(H3N2) viruses in children. During the 2014–2015 influenza season, widespread circulation of antigenically and genetically drifted A(H3N2) viruses provided an opportunity to evaluate subtype-specific vaccine effectiveness (VE) of quadrivalent LAIV (LAIV4) and IIV in children. Methods: Children (2–17 years) with febrile acute respiratory illness <5 days' duration were enrolled at 4 outpatient sites in the United States during the 2014–2015 influenza season. Nasal swabs were tested for influenza by reverse transcription polymerase chain reaction; vaccination dates were obtained from medical records or immunization registries. VE was estimated using a test-negative design comparing odds of vaccination among influenza cases and test-negative controls with adjustment for potential confounders. Results: Among 1696 children enrolled, 1511 (89%) were included in the analysis. Influenza was detected in 427 (28%) children; 317 had influenza A(H3N2) and 110 had influenza B. Most influenza isolates were characterized as a drifted strain of influenza A(H3N2) or a drifted strain of B/Yamagata. For LAIV4, adjusted VE was 50% (95% confidence interval [CI], 27–66%) against any influenza, 30% (95% CI, −6% to 54%) against influenza A(H3N2), and 87% (95% CI, 63–96%) against type B. For IIV, adjusted VE was 39% (95% CI, 18–54%) against any influenza, 40% (95% CI, 16–58%) against A(H3N2), and 29% (95% CI, −15% to 56%) against type B. Odds of influenza for LAIV4 versus IIV recipients were similar against influenza A(H3N2) (odds ratio [OR], 1.17; 95% CI, 0.73–1.86) and lower against influenza B (OR, 0.18; 95% CI, 0.06–0.55). Conclusions: LAIV4 and IIV provided similar protection against a new antigenic variant A(H3N2). LAIV4 provided significantly greater protection than IIV against a drifted influenza B strain. ClinicalTrials.gov identifier :NCT01997450